Epidemiology And Mortality Of Burn Injury In Ciptomangunkusumo Hospital, Jakarta: A 5 Year Retrospective Study - Wardhana, Aditya; Winarno, Gammaditya Adhibarata (Lingkar Studi Bedah Plastik Foundation, 2019)
Background : Burns is a significant cause of morbidity and mortality worldwide. Particularly in low- and middle-income countries (LMICs), burns account for an estimated 180.000 deaths every year. Burn-related mortality rates are exceptionally high in South-East Asia (11.6 deaths per 100 000 population per year) compare with much lower rates of 1.0 deaths per 100.000 people per year in high-income countries. This study aims to investigate the demographic data, etiology, and outcome of the patients treated in burn unit Ciptomangunkusumo Hospital, Jakarta, Indonesia. Method: This is a retrospective cross-sectional study, collecting epidemiologic data from the medical record through Electronic Health Record. A total of 709 patients admitted to burn unit between 2013-2017 were reviewed based on age, sex, total burn surface area (TBSA), burn grade, inhalation injury, etiology, length of stay, outcome, and payment method. Inclusion criteria are patients that were admitted to burn unit of Ciptomangunkusumo Hospital between 2013-2017, while there are no exclusion criteria in this study. Result : Admission of patients between 2013-2017 has inclined throughout the year, from 97 in 2013 to 166 in 2017. Average patient admission per year, reaching 141,8±26,761. Jakarta, and its suburb Bogor, Depok, Tangerang, and Bekasi, has dominated the proportion of referring hospital with 538(75.9%) The most amount of payment method is NHI (JKN/BPJS) with 534(75.3%) population. A total of 465 were male, and 244 were female, with a ratio of 1.9:1. The highest incidence in terms of age group is 16-35 years old (269, with the average age of patients, is 29±19. The highest incidence of burn injury is caused by a stove gas explosion with 253(35.7%), followed by flame 189(26.7%). There are 63 out of 709 patients with inhalation injury, where the incidence rate is 8.9%. Patients admitted to the Ciptomangunkusumo burn unit has an average length of stay of 15 days hospitalization. The most frequent population of extent, staying >14 days is 21-30% TBSA (88). The mortality rate in the Ciptomangunkusumo burn unit is 25.8% (183), with the highest number of death came from TBSA >40% (136). Conclusion: A total of 709 patients were admitted to the Ciptomangunkusumo burn unit in Jakarta, Indonesia, over 5 years, with an average of 141 patients per year and an increase of 171% from 2013 to 2017. Most patients were diagnosed with >40% TBSA and 2nd-3rd grade burn injury. An average of 15 days of hospitalization for patients leading up to 25.8% mortality rate, they are with septic shock as the most common condition causing death in the burn unit.